A COMPARATIVE ANALYSIS OF THE PRACTICE OF THE UNITED KINGDOM AND MALAYSIA IN RESPECT OF FREEDOM OF EXPRESSION (UUM Journal of Legal Studies, 2011)
International law, particularly treaties on human rights, has great influence on the development of the right to freedom of expression. The application of international treaties is very much dependant on the constitutions of individual countries and these constitutions to a large extent are dissimilar from one to another. The position in the United Kingdom is relatively unique since the country has no codified written constitution to safeguard the fundamental right to freedom of expression and as a result it was regarded as residual in nature. Nonetheless, the provisions of the international treaties, particularly the European Convention on the Protection of Human Rights and Fundamental Freedoms (ECHR) have altered this position and accordingly freedom of expression has been formally incorporated into the UK law via the Human Rights Act 1998 (HRA). Meanwhile, the international human rights treaties is considered to have less influence in Malaysia arguably since the country has a written constitution (the Federal Constitution) that contains a specific part on fundamental liberties including the right to freedom of expression.Keywords: International law, treaties, freedom of expression.